The Organization of â€œSenam Ayo Menyapuâ€ - Ramadhan, Muhammad Roviq Nur (Universitas Negeri Semarang (Unnes), 2018)
his research aimed to see in detail the implementation of senam ayo menyapu (â€œLetâ€™s sweepingâ€ gymnastic) activity from planning, organization, socialization, and implementation to its benefit to Surakarta Cityâ€™s government and people. The method employed in this study was descriptive qualitative method. The result of research explains recreation sport activity in Surakarta City responded to enthusiastically by the people as they are aware of the importance of health. However, in the implementation of sport activity, people often ignore cleanliness. As Adipura City, Surakarta has a program based on 3WMP: waras (healthy), wasis (smart), wareg (satisfied), mapan (steady) and papan (shelter). Senam ayo menyapu is the gymnastic using palm rib broom. Senam ayo menyapu activity was arranged in Solo menyapu day celebration exactly on June 08. The planning of organizing senam ayo menyapu was conducted in Living Environment Service and TISA Competency Test Place. Socialization process was conducted by teaching gymnastic movement to the people in various institutions by gymnastic instructor. Online media such as youtube, facebook and VCD are used to introduce senam ayo menyapu movement. The process of implementing senam ayo menyapu was conducted usually on Friday and Sunday in many institutions. The benefit of gymnastic could be seen from 320 of 376 (85.10%) respondents loving sport and 56 (14.8%) not loving sport. About 275 (85.93%) respondents loved senam ayo menyapu activity and 45 (14.06%) did not love it.